Future skill needs for the green economy - (:unkn) unknown (Publications Office of the European Union, 2009)
"Europe set the pace in the drive to a low-carbon economy. The expansion of the green economy is being accelerated by concerns relating to energy generation, resource use and environmental management. Skills are a critical ingredient in coherent education, training, employment and environmental objectives. This publication is based on the Cedefop workshop on future skill needs for the green economy, which presented research results of several recent studies on green skills and green jobs, in Thessaloniki, on 6 and 7 October 2008. Case studies present emerging skill needs, the changing qualification needs in jobs for renewable energies and skill profiles in environment and eco-innovations. Climate change mitigation policies represent a serious challenge for education systems and employment in Europe. All occupations will need greening, with a spectrum from those new jobs focused solely on delivering green goods or services to those that will require more limited changes to improve energy efficiency and reduce resource use. Workers from all walks of life need to expand their skill sets so they can help safeguard the environment." (Autorenreferat, BIBB-Doku)
Keywords: S 6.4.8.1 Umweltberufe; G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.3 Qualifikationsentwicklungen; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.1 Deutschland; I 2.2.2 Osteuropa; I 2.2 Europa; Umweltindustrie; Umweltberuf; Qualifikationsbedarf; Qualifikationsanforderung; Qualifikationsanpassung; Neue Tätigkeitsfelder; Neuer Beruf; Klimaschutz; Erneuerbare Energie; Internationaler Vergleich; Fallbeispiel; Großbritannien; Bundesrepublik Deutschland; Slowakei; Spanien; Europäische Union